The dictionary of fashion history - Cumming, Valerie; Cunnington, C. Willett; Cunnington, Phillis; Beard, Charles Relly; Cunnington, C. Willett (Oxford ; New York : Berg, 2010)
"A Dictionary of English Costume by C. Willett Cunnington. Phillis Cunnington and Charles Beard was originally published in 1960. A monumental achievement and encyclopaedic in scope, it was a comprehensive catalogue of fashion terms from the mid-medieval period up to 1900. It was reissued and updated several times, for the last time in 1976. For decades it has served as a bible for costume historians. The Dictionary of Fashion History completely updates and supplements the Cunningtons' landmark work to bring it up to the present day. Featuring additional terms and revised definitions, this new edition represents an essential reference for costume historians, students of fashion history, or anyone involved in creating period costume for the theatre, film or television. It is also fascinating reading for those simply interested in the subject. Clear, concise and meticulous in detail, this essential reference answers countless questions relating to the history of dress and ador generations to come. 'A welcome needed update of an early landmark dictionary on dress: a must have for all who care about the A to Z of fashion.' Joanne B. Eicher, Regents Professor Emerita at the University of Minnesola. 'Nearly forty years on and now hard to find save in reference libraries, the volume reappears as 'The Dictionary of Fashion History,' skilfully enlarged and re-edited by Valerie Cumming, formerly Deputy Director of the Museum of London. Given fresh life and thorough coverage from 1900 through the present day, the new dictionary is once again ready to prove itself a trustworthy guide and companion to all those interested in the absorbing study of clothing.' Ann Saunders, Editor. 'Costume' (1967-2007)"--BOOK JACKET.
"Based on A dictionary of English costume, 900-1900 by C.W. and P.E. Cunnington and Charles Beard, now completely revised, updated and supplemented to the present day by Valerie Cumming."
Keywords: Clothing and dress -- History -- Dictionaries; Fashion -- History -- Dictionaries